The design, development and evaluation of ibrt module for esl reading comprehension among malaysian secondary school learners - Ting, Pick Dew (2022)
This study aimed at designing and developing an Inquiry-Based Reciprocal Teaching (IBRT) Module to assist Malaysian ESL educators in improving their reading comprehension instruction with the intent of developing their learners’ reading comprehension through a methodical, attainable, and consistent use of reading strategies, as well as evaluating the effects of this module on ESL learners’ reading performance. This study adopted a modified design and developmental research approach with the ADDIE framework, which was carried out in three phases. The needs of 282 Form Four ESL learners in Penampang, Sabah were identified during the needs analysis phase, and further supported by the perspectives of 12 ESL educators in the same district. The design and developmental phase obtained the views and decisions of seven experts on the overall design, strategies, and activities in the module prior to the implementation of the module through a quasiexperimental pre-test-post-test group design in one of the secondary schools in Penampang. Two groups of Form Four ESL learners with equivalent characteristics; the experimental group (n = 42) and the control group (n = 42), were involved in this part of the study. Their reading performance was analysed using the pre-test and post-test mean scores. The main findings indicated that the post-test mean scores of the Form Four ESL learners who were exposed to the newly-developed module was significantly higher than those ESL learners exposed to the traditional approach, with t (82) = 9.71, p > .05, d = 0.52, indicating a medium effect size. The module also resulted in the ESL learners’ change of perceptions towards reading comprehension. The implications of this study shed light upon the current pedagogical approach to teaching reading comprehension, which provides a guideline for ESL educators in lesson planning and an auxiliary tool for teaching and learning reading comprehension.